Industrial training report: Medical Records Department, Hospital Kuala Lumpur / Nurhamiza Amir - Amir, Nurhamiza (Bachelor of Information Science (HONS.) Records Management, 2015)
For five months from February 2015 until June 2015, I did an intemship at Hospital Kuala Lumpur, a govemment hospital which cover many patients especially who live at Kuala Lumpur or any nearest area. I worked on my assignment project to investigate filing system and combine filing system in pediatric record department. The main content of the project is to find the best ways to overcome problem that happen in the pediatric record department. This topic suitable with my major which is records managements and help me to gain new experiences and many knowledge. But more importantly, I had a great experience in working environment. I also leams and apply my communications skills through discussing with the supervisors, others staffs and also publics/patients.